PEMIKIRAN FILSAFAT POLITIK ABDOLKARIM SOROUSH - Adi Bunardi (Sekolah Tinggi Agama Islam Sadra, 2021)
The ideas of freedom, justice, democracy, and secularism are the main themes in the study of political philosophy. In the context of religious and political relations, conversations about justice, democratic freedom, and political secularism are the main themes in the Islamic world. One of them is the debate on philosophical political thought that took place in Iran, after the revolution. The idea of ​​the relation between religion and politics, especially the relation between Islam and democracy which requires freedom and justice, has become an ongoing and ongoing philosophical political discourse. The main figure who became the vanguard in building religious and political relations based on freedom and justice was Abdolkarim Soroush. By using interpretive descriptive analysis and literature study coupled with a historical approach, this article attempts to explain Abdolkarim Soroush's view on the relationship between religion and politics, especially Islam and democracy with the themes of freedom, justice, secularism, and restricted democracy. The results obtained regarding the fundamental difference between political secularism and philosophical secularism according to Soroush are the roots and objectives. Soroush believes that political secularism is an alternative in solving the problem between religion and politics, both in religious societies and in non-religious or secular societies. Regarding democracy, Soroush views democracy as an anti-tyranny theory. As for justice, he considers justice to have roots in Islamic teachings and to be the basis of modern political life. In terms of freedom, Soroush views freedom as dynamic. Soroush divides the concept of freedom into political and philosophical, in the political dimension, freedom is identical with democracy.